Grafites do amor, da paz e da alegria na cidade Olímpica: interfaces entre política, arte e religião no Rio 2016 - Christina Vital da Cunha (Ciências Sociais Unisinos)
The objective of this article is to analyze the meanings attributed by different actors to graffiti, stencils and murals that form a motivational landscape in Rio de Janeiro in the context of the 2016 Olympics. Speeches, images and legislation conform the situations from which we propose this analysis having been systematized in ongoing research pro- jects funded by CNPq and the Universidade Federal Fluminense. Interviews were carried out with graffiti artists and representatives of the city council and a cartography of the productions present, mainly in the South Zone of Rio de Janeiro. The cut of the survey covering graffiti and other interventions mainly in the South Zone is justified by the importance that this territory of the city assumes politically for the external projection of this “Carioca spirit”, especially in the Olympic context.